Análisis empírico de la relación entre investigación, desarrollo, innovación, y crecimiento económico en países OCDE; Empirical analysis of the relationship between research, development, innovation, and economic growth in OECD countries - Juan Camilo Villar Otálora; Jacobo Campo Robledo (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– Taking a sample of 24 OECD countries, using a cointegrated panel, empirical evidence is provided at group and individual level of the positive effect of spending on research, development and innovation on economic growth during the 2000-2019 period. Assuming that patents act as a proxy for innovation and using the ordinary least squares dynamic estimator, the existence of a long-term equilibrium relationship is corroborated by which, and in per capita terms, an increase of 1.0 % in the stock of patents generates an increase in GDP of 0.52 %. Similarly, an increase in R&D spending of 1.0 % translates into GDP growth of 1.27 %. Additionally, by implementing a Granger causality test for a panel, a positive and significant relationship is found between R&D spending and the stock of patents, patent stock and economic growth, and R&D spending and economic growth.
Keywords: C33; O30; O38; O40; 330; R&D Spending; Innovation; Patents; Economic Growth; Cointegrated Panel; Granger Causality